Cryptosporidiosis in dogs bred in rural communities of Puno, Peru - Celis S., Noemit (2015)
The aim of this study was to determine the prevalence of Cryptosporidium sp in dogs of rural communities located in the districts of Ajoyani, Carabaya province and Palca and Santa Lucia, Lampa province, in Puno, Peru. Fecal samples were collected (n=123) from apparently healthy dogs of both sexes, older than one month. The ZiehlNeelsen modified technique was used for the diagnosis of Cryptosporidium sp. The overall prevalence was 26.8 ± 7.8% for Cryptosporidium sp and without significant association between the presence of the protozoa with the district, sex and age. The results show the presence ofCryptosporidium sp in dogs evidencing a possible zoonotic risk.